2007
DOI: 10.1007/s11099-007-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of H<sub>2</sub>O<sub>2</sub> on cyanobacterial photosynthesis

Abstract: The sensitivity of phytoplankton species for hydrogen peroxide (H 2 O 2 ) was analyzed by pulse amplitude modulated (PAM) fluorometry. The inhibition of photosynthesis was more severe in five tested cyanobacterial species than in three green algal species and one diatom species. Hence the inhibitory effect of H 2 O 2 is especially pronounced for cyanobacteria. A specific damage of the photosynthetic apparatus was demonstrated by changes in 77 K fluorescence emission spectra. Different handling of oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 26 publications
4
58
0
Order By: Relevance
“…The observed increase of basal chlorophyll fluorescence (F 0 , Fig. 4A, B), which is similar to that described by Drabkova et al (2007bDrabkova et al ( , 2007c, could thus be caused either by (1) inhibition of photosystem II function, or (2) elevated fluorescence yield from phycobilisomes or free phycobiliproteins. According to Campbell et al (1998), some phycobilisomes are uncoupled to the photosynthetic apparatus.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed increase of basal chlorophyll fluorescence (F 0 , Fig. 4A, B), which is similar to that described by Drabkova et al (2007bDrabkova et al ( , 2007c, could thus be caused either by (1) inhibition of photosystem II function, or (2) elevated fluorescence yield from phycobilisomes or free phycobiliproteins. According to Campbell et al (1998), some phycobilisomes are uncoupled to the photosynthetic apparatus.…”
Section: Discussionsupporting
confidence: 88%
“…Compounds that mainly produce hydroxyl radicals seem to be even more promising for treating cyanobacterial water-blooms, because they have significantly higher toxicity to cyanobacteria than to green algae (Drabkova et al, 2007a). This is especially true of hydrogen peroxide (H 2 O 2 ), a wellknown source of hydroxyl radicals, which has been found to be ten times more toxic to cyanobacteria than to green algae and diatoms (Drabkova et al, 2007b(Drabkova et al, , 2007c. Besides direct toxicity to cyanobacteria, it has also been demonstrated that H 2 O 2 exposure may decrease the transcription of the microcystin transport gene in Microcystis aeruginosa cells, which could potentially prevent the transport of this most significant cyanotoxin into the water system (Qian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…HP has been empirically tested as a cyanocide and/or general algicide by a range of authors, and widely deviating dose-response observations for effectiveness of HP versus cyanobacteria in lakes range from as much as 100 mg L -1 (Barrington and Ghadouani 2008; Barrington et al 2011Barrington et al , 2013 to around 60 mg L -1 (Wang et al 2012;Gao et al 2015), 10 mg L -1 (Jia et al 2014), to \5 mg L -1 (Barroin and Feuillade 1986;Drábková et al 2007b;Matthijs et al 2012). However, it is obvious that the higher the concentration of HP applied, the higher the killing efficiency of cyanobacteria will be, and conversely it must be argued that in lake treatments the dose should be as low as possible to avoid killing of non-target species and to respect the principle of sustainability.…”
Section: Mode Of Action Of Hydrogen Peroxidementioning
confidence: 99%
“…Although PSII photoinactivation continually occurs under regular and stable growth conditions, it may increase under environmental stress conditions that induce an increase in the rate of ROS formation (Long et al, 1994;Hirayama et al, 1995;Asada, 1999;Latifi et al, 2005;Nishiyama et al, 2006;Takahashi and Murata, 2008). Furthermore, photoinhibition induced by ROS seems to be higher in cyanobacteria than in other phytoplanktonic organisms (Drabkova et al, 2007).…”
mentioning
confidence: 99%